Pengaruh Penghindaran Pajak dan Kinerja Keuangan Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Pusphitasari, Pusphitasari; Indradi, Donny (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Maintaining and increasing company value is a crucial element in business competition, where owners and investors measure success through stock value and financial performance. This study analyzes the elements that affect the value of companies in the consumer non-cyclicals sector on the Indonesia Stock Exchange for the period 2018-2022. The results show that tax avoidance and financial performance influence company value, while company size moderates the impact of tax avoidance but does not moderate the impact of financial performance on company value. The study also reveals that although tax avoidance is legal, it can reduce investor confidence if not accompanied by information transparency. This study has several limitations, such as the sample being limited to the consumer non-cyclicals sector on the Indonesia Stock Exchange and the observation period of five years, which includes the pandemic period. The variables used in this study are also limited, which may not cover all factors affecting company value. Therefore, further research with a broader scope and additional variables is needed for more comprehensive results. In a broader context, this study emphasizes the importance of financial information transparency and compliance with tax obligations in maintaining investor confidence. Companies need to manage finances effectively and efficiently to achieve optimal performance and increase company value, which will ultimately attract investor interest and trust.